(3bGfhf GdJLGQI GdOhdjIs - (3WGdH MSf(B, (3ehSis ((3YeGf(B:s (3OGQ GdKbGaI(B,s, 2010)
(3NUGFU bGfhf GdJLGQI GdOhdjI h JhMjO gPG GdbGfhf GdeHGOF GdYGeI GdJj Jbhe YdjgG GJaGbjI GdCee GdeJMOI HTCf GdHjY GdOhdj ddHVGFY h fWGb JWHjb gPg GdGJaGbjI (B( (3GJaGbjI ajjfG (B) (3h Jchjf YbO GdHY GdOhdj , GdJYQja HGdJMcje GdJLGQj GdOhdj , GdeMce h GLQGAGJ JYjjfg h JfajP GdbQGQ GdJMcjej (B.s
(3eQGLY U(B.275 (3; edGMb U(B.282s
Keywords: (3GdJLGQI GdNGQLjIs; (3GdYdGbGJ GdNGQLjIs; (3GdbGfhf GdOhdjs